Internalization of Tamansiswa Teachings in The 21st Century in Geography Subjects - Fajar Bayu Priyambodo; Supardi; Andri Estining Sejati (Universitas Negeri Surabaya, 2023)
The 21st century adjustment in the field of technology one of them is Education. Education must be able to aspire to a generation that is adaptive and contextual to nature, geography subjects that were initially less desirable by students must adapt to an era that demands compatibility and still carries the noble value of Tamansiswa's teachings. This study aims to 1. Describe Tamansiswa's teachings that are relevant in the 21st century, 2. Analyzing the internaliasai of Tamansiswa's teachings in the 21st century in geography subjects. This research uses the literature review method which is a series of activities related to the method of collecting information from the library, reading, recording, and processing materials. This method is by describing articles related to the internalization of tamansiswa teachings in the 21st century in geography subjects. The results showed that problems in cognitive, affective and psychomotor aspects that have been educational challenges can be solved if the students' Park teachings are applied properly. The benefits of the teachings of the pancadharma of nature in geography subjects are used as a basis for consideration of proposed street names with toponymy techniques. The Education Tricenter can be modeled in outdoor study learning to shape the collaborative spirit of students according to the demands of the 21st century. Geography learning planning can refer to the Tri-Nga concept to produce teacher skills and learners in the 21st century.